"You say tomatoe, I say tomawto": The importance of deliberate practice for improved performance. (3rd July 2019) - Miller, Scott D.; Chow, Daryl; Wampold, Bruce; Hubble, Mark A.
ABSTRACT: In recent years, McNamara, and associates Hambrick and Oswald, conducted and published studies which purportedly showed deliberate practice exerts less powerful main effects than presented and popularized in the press, public discourse, and professional circles. Their central aim seemed to be one of correcting a particular misperception, as they surmised – the idea that time engaged in activity, compared to other factors – matters all that much. In a reanalysis, we distinguished between deliberate practice, strictly defined, and mere time spent. As it is, between the groups of researchers, the findings obtained are quite similar, hardly cause for objection or continuing debate.